Group cell FuTURE B3G TDD system - Xiaofeng Tao; Jin Xu; Xiaodong Xu; Chao Tang; Ping Zhang (2005 IEEE 16th International Symposium on Personal, Indoor and Mobile Radio Communications, 2005)
This paper introduces a general framework of B3G (Beyond 3G) mobile communication system in China TDD (time division duplex) Special Work Group. System architecture is described that allows the integration of multiple antenna techniques, e.g., MIMO (multiple input multiple output), in physical layer and the novel cellular architecture, e.g., group cell, in network layer. MIMO techniques based on group cell architecture, including spaced MIMO, distributed MIMO and virtual MIMO, are presented. What's more, a multi-MIMO matrix detection algorithm for distributed MIMO structure in Group Cell B3G TDD system is also presented and analyzed with the corresponding mathematical model. Link-level and system-level simulation results show the performance and capacity of this group cell MIMO system respectively